HPV self-sampling in CIN2+ detection: sensitivity and specificity of different RLU cut-off of HC2 in specimens from 786 women. Issue 4 (26th September 2016) - Bottari, F; Igidbashian, S; Boveri, S; Tricca, A; Gulmini, C; Sesia, M; Spolti, N; Sideri, M; Landoni, F; Sandri, M T
Abstract : Aims: Mortality for cervical cancer varies between the different regions of the world, with high rates in low-income countries where screening programmes are not present and organised. However, increasing screening coverage is still a priority in all countries: one way to do that is to base screening on self-sampled screening. The success of a self-sampling screening strategy depends on capacity to recruit unscreened women, on the performance and acceptability of the device and on the clinical performance of the high-risk human papillomavirus (HPV) test. Methods: This study based on 786 enrolled women investigates the best cut-off value of Hybrid Capture 2 HPV test (HC2) for self-sampled specimens in terms of sensitivity and specificity. Results: In this population, we found that the sensitivity and the specificity for cervical intraepithelial neoplasia grade 2 or more detection of HC2 performed on self-sampled specimens were 82.5% and 82.8%, respectively considering the relative light units (RLU) cut-off value of 1. Increasing the cut-off value the sensitivity decreases and the specificity raises and the best area under the curve for the RLU cut-off value is 1. Conclusions: Our results confirm that the cut-off value of 1 suggested by Qiagen for PreservCyt specimen is the best cut-off value also for self-sampled specimens.